“Exploring academic English writing skills in pre-service teachers for professional development” - Galvez Cardenas, Nathaly Johanna (2022)
Academic writing is a skill that allows develop in the academic and professional environment. To master this skill requires knowledge about skills and concepts that help in written production. However, writing and especially academic writing has been a problem in the academic development of students, especially in the eighth level students of the English course at the Technical University of Cotopaxi. These students have difficulty in mastering academic vocabulary, connectors of ideas and, especially, difficulty in organizing their ideas. All the difficulties mentioned above have been reflected in their level of academic writing when presenting their essays. Therefore, the objective of this research is to determine the skills to develop academic English writing in pre-service teachers for professional development. The methodology used in this project is qualitative and descriptive because it explains and describes the main problems that pre-service teachers present in academic writing texts. The results reflect that indeed the pre-service teachers possess a low level of academic writing skills. The researchers identified that the analysis of the writing results was low of clarity in texts, poor context sentences, as well as inadequate application of English as a second language because they use translator.